2021
DOI: 10.1111/ecc.13498
|View full text |Cite
|
Sign up to set email alerts
|

The psychosocial impact of living with mesothelioma: Experiences and needs of patients and their carers regarding supportive care

Abstract: Objective: Mesothelioma is a rare cancer with a poor prognosis caused by exposure to asbestos. Psychosocial support and care for mesothelioma patients and their carers is limited and not tailored to their specific needs. The aim of this study was to explore patients' and carers' needs and experiences regarding psychosocial support and their coping mechanisms dealing with psychosocial problems.Methods: A qualitative study was performed using semi-structured interviews with both mesothelioma patients and their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Specialist psychological support had rarely been accessed by patients or their carers. This reflects findings from other studies,9 26 and suggests improved access to tailored emotional support for patients and carers is important for long-term survivors.…”
Section: Discussionsupporting
confidence: 83%
“…Specialist psychological support had rarely been accessed by patients or their carers. This reflects findings from other studies,9 26 and suggests improved access to tailored emotional support for patients and carers is important for long-term survivors.…”
Section: Discussionsupporting
confidence: 83%
“…According to patients, psychological information and support should be offered from the initial diagnosis onwards and should include both themselves and their close relatives. 48 Patients in our study considered peer support a valuable type of psychosocial support, and previous research has shown it could improve patients' psychological empowerment (e.g. increased selfefficacy and positive coping) 49 and enable social reintegration 50 and return to work.…”
Section: Discussionmentioning
confidence: 79%
“…This need includes psychological support, and also the previously mentioned work‐related information and support. According to patients, psychological information and support should be offered from the initial diagnosis onwards and should include both themselves and their close relatives 48 . Patients in our study considered peer support a valuable type of psychosocial support, and previous research has shown it could improve patients’ psychological empowerment (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…It was striking that some bereaved family members thought that their input into PPI activities is less valuable than that of people diagnosed and living with mesothelioma because they are not the direct beneficiaries of research. This may indicate lack of awareness that mesothelioma research addresses family members’ (or carers’) needs, too [ 37 ], on reflection, something that the research team could have emphasised.…”
Section: Discussionmentioning
confidence: 99%